Clinician and parent views on urine collection in precontinent children in the UK: a qualitative interview study - Armengol, M; Hayward, G; Abbott, MG; Bird, C; Bergmann, JHM; Glogowska, M (BMJ Publishing Group, 2024)
Objective To explore the experiences of healthcare professionals (HCPs) and parents of urine collection methods, to identify barriers to successful sampling and what could improve the process. Design Qualitative research, using individual semistructured interviews with HCPs and parents. The interviews were audiorecorded, transcribed and thematically analysed. Setting UK-based HCPs from primary and secondary care settings and parents with experience with urine collection in primary and/or secondary care settings. Participants HCPs who were involved in aiding, supervising or ordering urine samples. Parents who had experience with urine collection in at least one precontinent child. Results 13 HCPs and 16 parents were interviewed. 2 participating HCPs were general practitioners (GPs), 11 worked in paediatric secondary care settings (8 were nurses and 3 were doctors). Two parents had children with underlying conditions where frequent urine collection was required to rule out infections. HCPs and parents reported that there were no straightforward methods of urine collection for precontinent children. Each method—‘clean catch’, urine bag and urine pad—had limitations and problems with usage. ‘Clean catch’, regarded as the gold standard by HCPs with a lower risk of contamination, often proved difficult for parents to achieve. Other methods had elevated risk of contamination but were more acceptable to parents because they were less challenging. Many of the parents expressed the need for more information about urine collection. Conclusions Current methods of urine collection are challenging to use and may be prone to contamination. A new device is required to assist with urine collection in precontinent children, to simplify and reduce the stress of the situation for those involved. Parents are key partners in the process of urine collection with young children. Meeting their expressed need for more information could be an important way to achieve better-quality samples while awaiting a new device.